(untitled) (Editora Impacto Científico, 2025)
Early Childhood Caries (ECC) is a prevalent pathology, resulting from the interaction between biofilm, diet and host factors, with serious repercussions on children’s quality of life. This narrative review examines current preventative and therapeutic strategies, highlighting that controlling ECC requires a multifaceted approach. The rational use of fluorides (toothpastes and varnishes) remains the gold standard of prevention. Antimicrobial alternatives, such as xylitol and probiotics, show comparable efficacy to chlorhexidine in reducing Streptococcus mutans, with fewer adverse effects. The study also emphasizes the influence of systemic factors, such as vitamin D deficiency on enamel formation, and social determinants, where family stability acts as a protective factor against disease progression. Integration of accurate diagnostics (ICDAS II) with educational and nutritional interventions is essential for effective management. DOI:https://doi.org/10.56238/edimpacto2025.093-006